2009
DOI: 10.2217/fon.09.91
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–Mesenchymal Transition in Hepatocellular Carcinoma

Abstract: The transition of epithelial cells to a mesenchymal phenotype is of paramount relevance for embryonic development and adult wound healing. During the past decade, the epithelial-mesenchymal transition (EMT) has been increasingly recognized to occur during the progression of various carcinomas such as hepatocellular carcinoma (HCC). Here, we focus on EMT in both experimental liver models and human HCC, emphasizing the underlying molecular mechanisms which show partial recurrence of embryonic programs such as TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
223
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(231 citation statements)
references
References 64 publications
4
223
0
Order By: Relevance
“…For different types of tumors it has been demonstrated that an EMT-switch is associated with a worse prognosis as seen in esophageal squamous cell carcinoom [81] , gastric cancer cells [82] bladder cancer [83] non-small cell lung cancer [84] and pancreas ductal adenomacarcinoma [85] . For HCC, this correlation has also been found with an independent effect of Twist and Snail in promoting metastasis of hepatocellular carcinoma [86][87][88][89] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 81%
See 1 more Smart Citation
“…For different types of tumors it has been demonstrated that an EMT-switch is associated with a worse prognosis as seen in esophageal squamous cell carcinoom [81] , gastric cancer cells [82] bladder cancer [83] non-small cell lung cancer [84] and pancreas ductal adenomacarcinoma [85] . For HCC, this correlation has also been found with an independent effect of Twist and Snail in promoting metastasis of hepatocellular carcinoma [86][87][88][89] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 81%
“…Important molecular pathway involved in EMT are Wnt/betacatenin signaling [95,96] and through growth factor signalling like PDGF [97] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 99%
“…EMT allows benign tumors to progress into metastatic cancers that can invade other tissues. 39 The evaluation and comparison of miRNAs in human cancers and EMT can provide insights into the type of miRNAs that regulate EMT to drive the transformation of tumor. In Table 2, we have summarized the EMT-associated miRNAs that have been identified and their target genes in various cancer types.…”
Section: Mirnas In Emt Transition and Cancer Metastasismentioning
confidence: 99%
“…23 In addition, the partial recurrence of embryonic programs, such as TGF-b and Wnt/b-catenin signaling, is present in HCC. 24 Nonetheless, the detailed signaling mechanisms of EMT and HCC metastasis is not well defined, and the growing body of respective studies has yet to reach consensus.…”
mentioning
confidence: 99%